Produtividade da canola em função das condições agrometeorológicas no Rio Grande do Sul - Silva, Jocélia Rosa da (2022)
Knowledge of the interaction between meteorological and/or environmental variables, their variability and canola crop productivity are essential for analyzing the variability of genotype performance for the spatial and temporal planning of this crop. Thus, the objectives of this study were: to determine the sub-period with the highest correlation between canola grain yield and the photothermal quotient and the photothermal quotient determination model with the highest correlation; to evaluate the yield of canola grains sown in a wide sowing period in different locations in Rio Grande do Sul, characterizing the relationship between maximum grain yield and meteorological elements. Yield and phenology data of different canola genotypes were collected in four municipalities in Rio Grande do Sul, in sowings from March to August (2010-2019). The relationship between canola grain yield and photothermal quotient was evaluated for different developmental sub-periods by the original method and its modifications. The sub-period from the beginning of flowering to the end of flowering was the one that showed the highest correlation between the photothermal quotient and productivity. Water deficiency and excess are stressful factors for canola plants, showing a linear decrease in maximum productivity with the increase of these stresses. The response of maximum canola grain yield is linear positive as the rate of satisfaction of water requirements increases. The maximum yield of canola is influenced by solar radiation, thermal and water conditions. Maximum yields of canola grains were obtained in sowings carried out from May to June.